KESIAPAN PEMERINTAH DAERAH DALAM PENERAPAN AKUNTANSI BERBASIS AKRUAL - Sulaiman Sulaiman; Abdullah Abdullah (JAFFA, 2016)
The purpose of this study is to demonstrate empirically whether human resources, infrastructure, information technology, organizational commitment, and accounting policies affect the readiness of the implementation of Government Accounting Standards based on accrual.The sample in this research is the employee who is in the sub-section of finance, assets, treasury and accounting fields, and field DPPKA budget of the city of Bengkulu. Respondents in this study amounted to 32 people. This study uses quantitative methods. The results of the study showed that the human resources, infrastructure, information technology, and organizational commitment positively affects the readiness of the implementation of Government Accounting Standards based on accrual. While the accounting policies are not influence on the readiness of the implementation of Government Accounting Standards based on accrual. The results of this study indicate that accounting understanding that each employee is not enough in the implementation of government accounting standards accrual basis.